2020
DOI: 10.31234/osf.io/b56qj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Ideological Attitudes in Responses to COVID-19 Threat and Government Restrictions in Australia

Abstract: Many government strategies to reduce the spread of Novel Coronavirus (COVID-19) involved unprecedented restrictions on personal movement, disrupting social and economic norms. Although generally well-received in Australia, some community frustration regarding these restrictions appeared to diverge across political lines. Therefore, we examined the unique effects of the ideological subfactors of Right-Wing Authoritarianism (RWA; Aggression, Submission and Conventionalism) and Social Dominance Orientation (SDO; … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Then, hierarchical regression models investigated whether the four ideologies predicted support for vaccine mandates and the punishment of unvaccinated individuals, with or without the inclusion of COVID-19 concern and vaccine acceptance. In prior research, these two factors are associated with ideological variables such as SDO, RWA, and libertarianism ( Bilewicz & Soral, 2021 ; Choma et al, 2021 ; Clarke et al, 2021 ; Murphy et al, 2021 ; Peng, 2022 ) as well as support for vaccine mandates ( Gagneux-Brunon et al, 2021 ). An inspection of the predicted probability plots and the residuals vs. predictor plots suggested that the assumptions for regression analyses were not violated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, hierarchical regression models investigated whether the four ideologies predicted support for vaccine mandates and the punishment of unvaccinated individuals, with or without the inclusion of COVID-19 concern and vaccine acceptance. In prior research, these two factors are associated with ideological variables such as SDO, RWA, and libertarianism ( Bilewicz & Soral, 2021 ; Choma et al, 2021 ; Clarke et al, 2021 ; Murphy et al, 2021 ; Peng, 2022 ) as well as support for vaccine mandates ( Gagneux-Brunon et al, 2021 ). An inspection of the predicted probability plots and the residuals vs. predictor plots suggested that the assumptions for regression analyses were not violated.…”
Section: Resultsmentioning
confidence: 99%
“…SDO reflects a preference for hierarchical intergroup relationships, justification of group-based dominance, and less empathy toward disadvantaged groups ( Pratto et al, 2013 ; Pratto, Sidanius, Stallworth, & Malle, 1994 ). SDO frequently predicts less concern about COVID, less adherence to public health guidelines, and less support for government measures ( Choma et al, 2021 ; Clarke, Klas, & Dyos, 2021 ; Fischer et al, 2020 ; Peng, 2022 ). Recent research also finds that SDO predicts more hesitancy against COVID-19 vaccines ( Bilewicz & Soral, 2021 ; Murphy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…An important limitation of our study was the use of an abbreviated RWA scale; therefore, future studies would need to determine whether the results are confirmed using the full version of the scale. Also, it would be worthwhile to include a measure of social dominance orientation - the second facet of political ideology, emphasizing a preference for hierarchy and high-status group dominance (see e.g., Clarke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a noteworthy finding, given the long-standing debate as to whether conspiracy theorizing is inherently connected with ideological predispositions (e.g., Sutton & Douglas, 2020b). Some have shown that susceptibility to conspiracy beliefs is higher amongst conservatives (see e.g., Enders & Smallpage, 2019; van der Linden et al, 2021), and reactance to COVID-19 government restrictions is predicted by various right-wing ideology subfactors (Clarke et al, 2021). Others argue that conspiracy beliefs are strongest amongst both extreme ends of the ideological spectrum, expressed to a similar extent by extreme right- and left-wing ideologues (van Prooijen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%